Flexural Strength of Lake Ice in Relation to Its Growth Structure and Thermal History. - Gow,Anthony J.; Langston,David (1975)
In-place cantilever beam tests on Post Pond and Mascoma Lake (N.H.) ice yielded a maximum flexural strength of 7.1 kg/sq cm. The minimum strength, unrelated to failure along pre-existing cracks in the ice, was 2.9 kg/sq cm. The majority of tests were performed in the push-down mode after it was discovered that beams tested in the pull-up mode, which places the bottom surface in tension, frequently broke prematurely along cracks in the bottom of the ice. Premature failures of this kind usually occurred at stresses of 2-3 kg/sq cm. Data further demonstrate that the intrinsic strength of lake ice decreases sigificantly as the surface air temperature goes to 0 C. Ice that has just become isothermal, but has not yet begun to candle, has a strength of about 4 kf/sq cm; ice that has been subjected to prolonged periods of above-freezing air temperatures generally fails at about 3 kg/sq cm. Tests also show that cold unrecrystallized snow-ice is as strong as the underlying lake ice. Tests of the effect of crystalline structure indicate that ice composed of crystals with their c-axes horizontal is measurably stronger than ice in which the crystals are oriented with their c-axes vertical. (Author)